Social Relationship Between Kampong Gendong Residents and Gated/Non-Gated Community in Sendangmulyo Village Tembalang District, Semarang - Retno Susanti; Retno Widjajanti; Grandy Loranessa Wungo; Intan Budiarti (Diponegoro University, 2020)
Population growth in the city of Semarang increases the need for residential land, shifting individuals from the center to the suburbs. Tembalang is a sub-district with a population growth of 3.69%. The trend in population growth is used to build gated homes, for middle and upper class individuals who need more comfortable, secure, quiet housing. However, the existence of a gated community makes a physical separation between community settlements. Privatization of public spaces in gated housing potentially leads to social inequality and lack of interaction with the surrounding community. The purpose of this study was to examine the social relations between the villagers around housing and residents of the gated community. The study uses questionnaires and open interviews interviews with 93 respondents from Kampong Gendong and a hierarchical analysis to examine social relations. The results show that there are social relations between gated housing residents and villagers based on residence, and they carry out several activities together. Also, housing typology influences the strength of the interaction between villagers and residents of the gated homes. In general, gated housing appear as a form of exclusive property with separate environmental facilities, which might be used by villagers to strengthen social interaction. The relations with the surrounding community play n important role in increasing the sense of security for residents of gated housing, unlike the use of perimeter fence or the guards.